Fare Integration in The Urban Public Transport: A Literature Review on Regulatory Perspective - Grzegorz DYDKOWSKI; Anna URBANEK (Communications of International Proceedings, 2022)
Transport integration is one of the most important means to advance sustainable transport and sustainable economic development. Sustainability and integration are complementary in transport policy and practice. Transport integration is a very complex issue, comprising both technological and organizational innovations. Although integrated transport as a common EU transport policy goal has a long history there are still many barriers to overcome to achieve integration in transport systems in practice at every level: local, regional, national and transnational. The paper presents the results of a literature review on the regulatory perspective of fare integration in public transport.
Keywords: fare integration; public transport; transport integration; mobility; transport policy